"Here's to a Night of Drunken Mistakes": Exploring Experiences, Regrets, and Optimism in Young Adult Drinkers. (10th November 2018) - Davies, Emma L.; Joshi, Mary Sissons
ABSTRACT: Background : Studies exploring "anticipated regret" concerning alcohol rarely consider the broader consequences of excessive drinking that might be regretted. Even if specific regrettable experiences are identified, interventions targeting them may not succeed because individuals are often optimistic about their risk susceptibility. Objectives : This study examined the consequences young adult drinkers reported, and the extent to which these were regretted. It then explored whether consequences and regrets differentiated between high risk, low risk and light drinkers, and whether regret was related to optimism. Methods : A cross-sectional on-line questionnaire measured drinking behavior, consequences (frequency) and regrets (extent of likely regret) and risk perceptions (in general, and compared to others). Results : 273 participants were recruited (light (30%), low-risk (40%), and high-risk drinkers (30%). PCA detected three types of experience (common—e.g., vomiting; after-effects—e.g., being depressed; and "serious"—e.g., drunk-driving), and three types of regret ("serious"—e.g., being aggressive; "common"—e.g., wasting time; and "risky behavior regrets"—e.g., drugs). Multinomial regression found the high-risk drink group more likely to be male, had more experiences but regretted these experiences less than other groups. Regrets and optimism interacted, so that higher scores on common regrets were associated with greater optimism. The high-risk group was particularly characterized by optimism. Conclusions : High-risk drinkers may be unresponsive to anticipated regret manipulations as they do not regret post-alcohol "bad" experiences, and some regrets were associated with comparative optimism. Interventions may need to focus less on regret and aim to change risk perceptions.